(untitled) (Texas Journal of Philology, Culture and History, 2023)
In this article, the concept of augmented reality is working on the mechanisms and applications in abstract paintings as augmented reality has a fundamental role in reviving the idea of abstract painting, which enables art lovers to enjoy painting more and accordingly changes the aesthetic standards. In addition, to utilize augmented reality, we can move abstract paintings from the stagnation of reality to a voluntary imagination. As well as augmented reality enables interior designers in displaying their designed projects before applying them in the real world. Thus, this assists art lovers to display an abstract painting in their houses, offices, hotels or every place before purchasing it which saves more money for the art lovers due to this application will help them imagine the decoration of interior design and select the most suitable to what they want and desire. İn addition to assisting fine arts students to express their artistic ideas through augmented reality